2012
DOI: 10.1590/s0006-87052012005000015
|View full text |Cite
|
Sign up to set email alerts
|

Altura da lâmina, tempo e volume de enchimento de um equipamento de irrigação por pavio e determinação da uniformidade de distribuição de água em substratos

Abstract: ResumoOs objetivos deste experimento foram realizar a avaliação da altura da lâmina de água, do tempo e volume de enchimento de um equipamento de irrigação por pavio usando calhas autocompensadoras e determinar a uniformidade de distribuição de água (UDA) nesse equipamento utilizando substratos orgânicos comerciais (casca de pinus/CP e fibra de coco/FC). Dois módulos experimentais foram montados em delineamento experimental inteiramente casualizado com cinco repetições. Verificou-se grande variação das medidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…These systems apply excessive amounts of water and, combined with the leaf interception as the plant grows (umbrella effect), leads to the irregular distribution of water, thus reducing irrigation efficiency. This method also increases the risk of environmental pollution due to the disposal of residual solution from fertigation (SCHMAL et al, 2011;FERRAREZI et al, 2012). It is estimated that between 49% and 83% of water applied through canopy irrigation is lost in the process and fails to reach the inside of the containers (DUMROESE; DAVIS; JACOBS, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems apply excessive amounts of water and, combined with the leaf interception as the plant grows (umbrella effect), leads to the irregular distribution of water, thus reducing irrigation efficiency. This method also increases the risk of environmental pollution due to the disposal of residual solution from fertigation (SCHMAL et al, 2011;FERRAREZI et al, 2012). It is estimated that between 49% and 83% of water applied through canopy irrigation is lost in the process and fails to reach the inside of the containers (DUMROESE; DAVIS; JACOBS, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The subirrigation method, by which water moves vertically by capillary rise in the substrate until it reaches the root system of plants, and can operate in an open or closed system, can potentially be used in crop production in protected environments, enabling a reduction of environmental and financial costs through resource conservation (SCHMAL et al, 2011 VAN IERSEL, 2011;MELLANO, 2011;FERRAREZI et al, 2013;MELO JUNIOR;GERVÁSIO;ARMINDO, 2013) have shown that subirrigation systems provide a more uniform and efficient application of solution, eliminating water and nutrient loss. These systems are made possible by automation and recirculation of the nutrient solution, and lead to increased production with better uniformity across the unit area, as well as reduced growth time.…”
Section: Introductionmentioning
confidence: 99%
“…Para isso, o pavio constituído de manta sintética não tecida é colocado na parte inferior de uma calha plástica de perfil trapezoidal, que é preenchida com o substrato (TESTEZLAF, 2011). O pavio conduz a solução nutritiva de um reservatório inferior para o substrato, e conforme ocorre o consumo pelas plantas, o pavio repõe a solução automaticamente por diferença de potencial total de água (FERRAREZI et al, 2012).…”
Section: 11sistemas De Subirrigaçãounclassified